CM 2022
DOI: 10.18137/cardiometry.2022.21.2733
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on free radical processes in the heart in rats with Guerin’s carcinoma and characteristics of malignant lesions depending on the gender of animals

Abstract: To study the intensity of lipid peroxidation (LPO) and the activity of the main antioxidant protection enzyme: superoxide dismutase (SOD) in heart tissues and tumors in rats of both genders with Guerin’s carcinoma (GC) and the tumor growth against the background of diabetes mellitus (DM). Materials and methods. Our research work was carried out in 80 outbread albino male and female rats, divided into 4 groups, with 10 animals of each gender in a group. The animals of two groups, namely, an intact animal group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the presented experimental works, bold attempts were made to implement the idea of how the mechanism is initiated and actuated, which is responsible for the behavior of tumors of various types is, up to genetically modified ones, under strictly specified conditions, in the presence of another pathological condition in the body: chronic pain or hypothyroidism, obesity or diabetes mellitus. The same profile of research, "model in model", has been revealed through the involvement of biochemical, electrophysiological, hormonal, morphological methods, the totality of the results of which states the possibility of predicting the ways of regulating the tumor process, metastasizing, life expectancy and gender differences [44][45][46][47][48].…”
Section: Pulses Of Extra-depolarization Of Switching-off Programmentioning
confidence: 99%
“…In the presented experimental works, bold attempts were made to implement the idea of how the mechanism is initiated and actuated, which is responsible for the behavior of tumors of various types is, up to genetically modified ones, under strictly specified conditions, in the presence of another pathological condition in the body: chronic pain or hypothyroidism, obesity or diabetes mellitus. The same profile of research, "model in model", has been revealed through the involvement of biochemical, electrophysiological, hormonal, morphological methods, the totality of the results of which states the possibility of predicting the ways of regulating the tumor process, metastasizing, life expectancy and gender differences [44][45][46][47][48].…”
Section: Pulses Of Extra-depolarization Of Switching-off Programmentioning
confidence: 99%